Roles for molecular chaperones in cystic fibrosis - Cyr, Douglas M. (Henry Stewart Talks, 2007)
Cystic fibrosis is a fatal homozygous recessive disorder, Caused primarily by misfolding of mutant forms of cystic fibrosis transmembrane conductance regulator (CFTR), The folding defects in mutant CFTR are detected by protein quality control machines in the endoplasmic reticulum that target mutant CFTR for premature degradation, Small molecules that are being developed as drugs to treat cystic fibrosis enable mutant CFTR to avoid recognition by the endoplasmic reticulum quality control system and function at the cell surface